Evaluation of plant protection efficacy in field conditions and side effects of Lysobacter capsici AZ78, a biocontrol agent of Plasmopara viticola. Issue 8 (3rd August 2022) - Markellou, Emilia; Kapaxidi, Eleftheria; Karamaouna, Filitsa; Samara, Maria; Kyriakopoulou, Katerina; Anastasiadou, Pelagia; Vavoulidou, Evangelia; Meidanis, Marios; Machera, Kyriaki; Mandoulaki, Athanasia; Margaritopoulou, Theoni; Giovannini, Oscar; et al.
ABSTRACT: Downy mildew, caused by Plasmopara viticola, is a highly significant grapevine disease causing severe yield losses and affecting wine quality. Disease control mainly relies on use of copper and synthetic fungicides. Today there is a growing interest in developing microbial biopesticides for downy mildew control in integrated and organic viticulture. Here, the bacterial biocontrol agent Lysobacter capsici AZ78 (AZ78) was tested following a holistic approach including in planta efficacy test (large-scale trial) combined with bioassays aiming to assess potential adverse effects on non-target organisms: beneficial arthropods ( Aphidius rhopalosiphi and Typhlodromus pyri ), the crustacean Daphnia magna, the algae Selenastrum capricornutum and soil organisms [earthworm Eisenia (Ei.) fetida and worm Enchytraeid (En.) albidus ]. Moreover, side effects of AZ78 treatments on grape quality and wine-making process were assessed. The results showed that AZ78 was equally effective to reference fungicide (Kocide®2000) in controlling downy mildew on leaves and bunches. AZ78 had no significant effect on the mortality of the indicator arthropod species at a Limit test Rate, which was equal to four times the recommended field rate. Additionally, no significant effects (mortality, growth rate or reproduction) were observed on D. magna, Ei. albidus, En. fetida and S. capricornutum, indicating AZ78 low toxicity on non-target organisms. Likewise, the yeast population dynamics in fermenting musts was not affected, without compromising the fermentation processes and wine quality. Overall, this study provides new insights into the characterisation of the biocontrol agent AZ78 showing that this bacterium has the potential to be further developed as a commercial biopesticide.